Propositional Objects: An Organizational Policy Mediated by Documents [Objetos Proposicionales: Una Política Organizacional Mediada por Documentos] - Castillo-Sepulveda, J; Bywaters-Collado, F; Galvez-Ramirez, M (Universitat Autonoma de Barcelona, 2021)
Documents have been an important part of organisational formalization and transformation. This has been particularly evident in the medical field. In this work we analyze the actions promoted by documents such as clinical practice guidelines. We carried out focused ethnographies, interviews, and documentary analysis in design spaces, as well as in care centres. For the analysis, we adopted actor-network theory perspective. This approach has allowed us to point out how the guides inscribe relationships that are interpreted locally, establish co-affection links as they modify and are modified by the clinical scenarios, and participate in pragmatic arrangements to formulate clinical effects. Finally, and adopting elements of Whitehead s process philosophy, we consider that these can be conceived as propositional objects. These objects collect the normative potential of a scenario, offer opportunities to be introduced into relationships and, likewise, guide its course. © 2021 Universitat Autonoma de Barcelona. All rights reserved.